An emerging issue: Social media addiction and its ill effects on medical students of Punjab - Aditya Ahuja; Paresh Prajapati; Ruchita Lunagariya; Rohit Bhowmick; Sachi Jain; Tanvir Kaur Sidhu (Journal of Family Medicine and Primary Care)
Background: Social networking sites (SNS) are widely used by millions of people. Excess use of social media leads to addiction which is controlling lives of young generation leading to harmful effect on their physical, mental and social well-being. Aim and Objective: To find the prevalence of social media addiction among government and private medical college students across Punjab and uncover the ill effects of social media addiction on physical and mental health, relationships etc. Materials and Methods: In this cross-sectional study, 717 students were included by convenience sampling technique. A reliable and validated questionnaire of previous studies was used along with self-designed questionnaire. Data were collected in Google forms and analyzed in MS Excel. Results: Out of total 717 students, majority (46.30%) of the students were using internet for 4–6 hours per day. Overall prevalence of addiction among MBBS students was found to be 8.64%. In physical health, sleep deprivation leading loss of concentration was the major health issue. Mood alterations due to chats of social media found to be significantly more in females than male students. Also, 64.15% of students agreed to have negative effect of social media on their academic performances. Conclusion: Many students were self-described addicts, and addiction was felt more by government college students. In this study, it was found that social media addiction leads to many physical and mental health issues like sleep deprivation which leads to harmful effects on their academics as well as make them prone to many noncommunicable diseases.